Overcoming the senescence‐associated secretory phenotype (SASP): a complex mechanism of resistance in the treatment of cancer - Cecilia R. Chambers (Wiley, 2021)
Senescence is a cellular state in which cells undergo persistent cell cycle arrest in response to nonlethal stress. In the treatment of cancer, senescence induction is a potent method of suppressing tumour cell proliferation. In spite of this, senescent cancer cells and adjacent nontransformed cells of the tumour microenvironment can remain metabolically active, resulting in paradoxical secretion of pro‐inflammatory factors, collectively termed the senescence‐associated secretory phenotype (SASP). The SASP plays a critical role in tumorigenesis, affecting numerous processes including invasion, metastasis, epithelial‐to‐mesenchymal transition (EMT) induction, therapy resistance and immunosuppression. With increasing evidence, it is becoming clear that cell type, tissue of origin and the primary cellular stressor are key determinants in how the SASP will influence tumour development and progression, including whether it will be pro‐ or antitumorigenic. In this review, we will focus on recent evidence regarding therapy‐induced senescence (TIS) from anticancer agents, including chemotherapy, radiation, immunotherapy, and targeted therapies, and how each therapy can trigger the SASP, which in turn influences treatment efficacy. We will also discuss novel pharmacological manipulation of senescent cancer cells and the SASP, which offers an exciting and contemporary approach to cancer therapeutics. With future research, these adjuvant options may help to mitigate many of the negative side effects and protumorigenic roles that are currently associated with TIS in cancer.